2020
DOI: 10.1111/jnc.15254
|View full text |Cite
|
Sign up to set email alerts
|

Zinc‐α2‐glycoprotein relieved seizure‐Induced neuronal glucose uptake impairment via insulin‐like growth factor 1 receptor‐regulated glucose transporter 3 expression

Abstract: Glucose hypometabolism is observed in epilepsy and promotes epileptogenesis.Glucose hypometabolism in epilepsy may be attributed to decreased neuronal glucose uptake, but its molecular mechanism remains unclear. Zinc-α2-glycoprotein (ZAG) is related to glucose metabolism and is reported to suppress seizures. The anti-epileptic effect of ZAG may be attributed to its regulation of neuronal glucose metabolism. This study explored the effect of ZAG on neuronal glucose uptake and its molecular mechanism via insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…GC10289, Glpbio), a glucose uptake assay was performed as described previously. 14 2‐NBDG solution was diluted to 100 μM with glucose‐free neurobasal. Cells were seeded in plates.…”
Section: Methodsmentioning
confidence: 99%
“…GC10289, Glpbio), a glucose uptake assay was performed as described previously. 14 2‐NBDG solution was diluted to 100 μM with glucose‐free neurobasal. Cells were seeded in plates.…”
Section: Methodsmentioning
confidence: 99%
“…GLUT1 deficiency syndrome (GLUT1 DS) caused by GLUT1 deficiency indicates the types of variable focal and multiple local seizure, and electroencephalography (EEG) manifestations [ 103 ]. The 2-[N-(7-Nitrobenz-2-oxa-1,3-diazol-4-yl) amino]-2-deoxy-D-glucose (2-NBDG) method and glucose uptake colorimetric method have shown that seizures could dramatically reduce neuronal glucose uptake and GLUT-3 expression [ 104 ]. However, study on hippocampal neurons from cultured primary rats and hippocampal slices from mice [ 98 ] have demonstrated that adiponectin enhances glucose uptake, glycolysis rate, and ATP production through the AMPK -dependent mechanism.…”
Section: The Effects Of Adiponectin On Epilepsymentioning
confidence: 99%